Natureza, Terra e Economia Agropastoril - SOURE (CE): 1798-1860 - Duarte, Rones da Mota (2012)
This work seeks to understand the way of life of the farmers in Soure during the first 60 years of the nineteenth century, taking into account land access, agro-pastoral production and the relationship these people had with nature. First I shall consider the colonization process of the west coast of Ceará, which initiated the formation of an agro-pastoral zone destined for commercial purposes. To this end, I shall examine the first expeditions to be sent to this coast, and seek to identify, from the accounts left by Father Luis Figueira and Martins Soares Moreno, the landscape and natural features of the area found by the settlers. Conquest of the territory was later carried out by soldiers from the Fortress of Nossa Senhora da Assunção, who began to apply for land grants in the region. I therefore look at the social profile of those who received these grants, and the advance into indigenous lands that caused disputes between natives and settlers throughout the territory. I shall then look into the effects of the Land Law of 1850, which was intended to consolidate the agro-pastoral zone in this region, and from the land registry of the Parish of São José do Ribamar, and from post-mortem inventories, I shall identify forms of land access, size and location of properties, and the agrarian landscapes created up until 1860. Finally, I shall look at the agro-pastoral activities developed by these farmers, as well as their understanding of nature, as used in the quest for a better use of natural resources for agriculture activities, and the environmental impacts caused by planting techniques and the introduction of exotic plants into the ecosystems of Soure, which resulted in environmental changes and the creation of a new agrarian landscape.